PENGARUH SIKLUS BISNIS, KAPASITAS HUTANG, PROFITABILITAS DAN NILAI PASAR TERHADAP REAKSI PASAR PADA PERUSAHAAN MANUFAKTUR DI BURSA EFEK INDONESIA - Winston Pontoh (Media Riset Akuntansi, Auditing & Informasi, 2011)
Invesments for stocks has a high risk compared with the other investments. Ability of company to make earnings is very demanded by investors in their investments to get dividend and maximized capital gain.The ability of company can be view by some aspects, there are, business cycle by Degree of Operating Leverage (DOL), debt capacity by Debt to Equity Ratio (DER) and Interest Coverage Ratio (ICR), profitability by Return on Equity (ROE) and Earnings Per Share (EPS), and market value by Price Earnings Ratio (PER).The objectives ofresearch are to analyze effect ofDegree of Operating Leverage (DOL), Debt to Equity Ratio (DER), Interest Coverage Ratio (ICR), Return on Equity (ROE), Earnings Per Share (EPS), dan Price Earnings Ratio (PER) to market stock price. The research use data of audited financial statements of manufacturing company from Indonesia Stock Exchange (Bursa Efek Indonesia) in period 2007 till 2009.The results show that as partial, DOL, ROED, PER, EPS, and DER significantly effect to market stock price, than ICR. Simultaneously, DOL, ROED, ICR, PER, EPS and DER significantly effect to market stock price.